2003
DOI: 10.1590/s1413-86702003000200009
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of pediatric infections in a teaching hospital in Mato Grosso do Sul, Brazil

Abstract: Nosocomial infections (NI) result in considerably high mortality and morbidity rates, especially among pediatric patients. Considering current worldwide changes, information about the occurrence of pathogens and susceptibility tests are now seen as decisive for optimizing treatment. The purpose of this research was to determine the frequency of microorganisms, antimicrobial and genetic profiles, and risk factors associated with nosocomial infections in a teaching hospital in Campo Grande, Mato Grosso do Sul. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The hospital sector where cases of candidemia are most commonly found is the ICU, for besides being the place where patients find themselves more impaired, it also completes a routine of invasive procedures, probes, and long-term catheters 19,[27][28][29] . All the candidemia cases in this study were observed in patients in ICUs, a point that is also discussed by other studies that recognize the ICU as a place of utmost susceptibility to the incidence of such infection [30][31][32][33] . The absolute mortality rate due to candidemia was 23.1%, a result that is also consonant with the data provided by the bibliographic references [18][19][20] .…”
Section: Ethical Considerationssupporting
confidence: 70%
“…The hospital sector where cases of candidemia are most commonly found is the ICU, for besides being the place where patients find themselves more impaired, it also completes a routine of invasive procedures, probes, and long-term catheters 19,[27][28][29] . All the candidemia cases in this study were observed in patients in ICUs, a point that is also discussed by other studies that recognize the ICU as a place of utmost susceptibility to the incidence of such infection [30][31][32][33] . The absolute mortality rate due to candidemia was 23.1%, a result that is also consonant with the data provided by the bibliographic references [18][19][20] .…”
Section: Ethical Considerationssupporting
confidence: 70%
“…Currently, Gram-negative bacteria are still among the most important agents involved in pediatric bloodstream infections, responsible for approximately 24% to 50% of the cases [5,6,8,9,14]. We have also observed that the frequency of these agents presents variations according to region or medical service studied.…”
mentioning
confidence: 84%
“…Similarly, the amoxicillin + clavulanic acid (30μg/10μg) disk was placed 20mm apart. After incubating overnight at 37°C for 24 hours, a ≥ 5mm or more increase in the zone diameter around cefotaxime/clavulanic acid (CTX/Clav) was considered positive for ESBL production [11]. E.coli ATCC25922 was used as negative ESBL control.…”
Section: Esbl Detection Testsmentioning
confidence: 99%